Comprehensive monitoring of MEA degradation in a post-combustion CO2 capture pilot plant with identification of novel degradation products in gaseous effluents. (August 2016) - Chahen, Ludovic; Huard, Thierry; Cuccia, Lorena; Cuzuel, Vincent; Dugay, José; Pichon, Valérie; Vial, Jérôme; Gouedard, Camille; Bonnard, Leslie; Cellier, Nadège; Carrette, Pierre-Louis
Highlights: A pilot plant campaign was performed to study MEA degradation. Specific methods were developed for sampling, sample conditioning and analysis. Developed gas phase sampling enabled identification of 17 novel degradation products. Several derivatives of pyrazine, pyridine and oxazolidine were identified. 1H-pyrrole and a new nitrosamine, the N -nitroso-2-methyloxazolidine were identified. Abstract: A pilot plant campaign was performed to study MEA degradation in CO2 capture conditions and anticipate potential degradation products emissions to the atmosphere in industrial case. Aqueous 30% wt MEA was cycled between absorption and regeneration steps during 1700 h in the presence of a synthetic flue gas containing 81% of N2, 14% of CO2, 5% of O2, 97 ppm of NO, 9 ppm of SO2 and 5 ppm of NO2 . Specific methods (sampling, sample conditioning and analysis) were developed to improve degradation products identification and to provide a quantification of targeted compounds in liquid phase and above all in absorber and stripper gas effluents. Especially, trace elements were detected in liquid phase thanks to Head Space-Solid Phase MicroExtraction (HS-SPME) and liquid–liquid extraction with ChemElut cartridges and in gas phase thanks to adsorbent tubes of different type: Sep-Pak ® for aldehydes and ketones, Orbo 60 for N -nitrosodimethylamine, Tenax and active charcoal for non-specific adsorption. 32 degradation products were identified in liquid phase and 38 in gas phase, 17 of which for the first time, especially derivatives of pyridine and oxazolidine, 1H-pyrrole and a new nitrosamine, the N -nitroso-2-methyl-oxazolidine.